2012
DOI: 10.1016/j.jpain.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Pain-Related Fear and Catastrophizing Predict Pain Intensity and Disability Independently Using an Induced Muscle Injury Model

Abstract: Timing of assessment of psychological construct is controversial and results differ based on the model of pain induction. Previous studies have not used an exercise induced injury model to investigate timing of psychological assessment. Exercise induced injury models may be appropriate for these investigations because they approximate clinical pain conditions better than other experimental stimuli. In this study we examined the changes of psychological constructs over time and determined whether timing of asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 42 publications
5
85
1
1
Order By: Relevance
“…Anxiety, manifested by increased emotional and physiological arousal, is known to be related to chronic pain 50 and to pain hyperresponsiveness among chronic pain patients 33 and healthy subjects 48 . Pain-related expressions of anxiety, namely pain catastrophizing and anxiety sensitivity, which are also prevalent in PTSD 37,61 were also shown to be related to pain hyperresponsiveness among chronic pain patients and healthy individuals 47,58 . However, the relationship between anxiety and pain perception in PSTD has not been systematically studied.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 94%
“…Anxiety, manifested by increased emotional and physiological arousal, is known to be related to chronic pain 50 and to pain hyperresponsiveness among chronic pain patients 33 and healthy subjects 48 . Pain-related expressions of anxiety, namely pain catastrophizing and anxiety sensitivity, which are also prevalent in PTSD 37,61 were also shown to be related to pain hyperresponsiveness among chronic pain patients and healthy individuals 47,58 . However, the relationship between anxiety and pain perception in PSTD has not been systematically studied.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 94%
“…Not all studies have shown independent contributions of pain catastrophizing and fear of pain to adverse pain outcomes, and the magnitude of relations between pain catastrophizing, fear of pain and pain outcomes has varied as well 3,23, 24, 34,50 Psychology of multisite pain 21 Note: N = 119. PCS = Pain Catastrophizing Scale; FOP-III-SF = Fear of Pain Questionnaire -III -Short Form; PHQ-9 = Patient Health Questionnaire -9; For correlations with Pain Intensity S2, Pain Intensity S1 was controlled; for correlations with Multisite Pain S2, Multisite Pain S1 was controlled.…”
Section: Psychology Of Multisite Pain 17mentioning
confidence: 99%
“…For instance, those who have experienced acute and/or chronic orofacial pain are more likely than those who have not to later report fear of pain (van Wijk and Hoogstraten 2005). Furthermore, those with higher levels of fear of pain are more likely to perceive pain stimuli as more intense (van Wijk and Hoogstraten 2009), to engage in pain catastrophizing (Parr et al 2012) and avoidance behaviors that worsen chronic pain (Lee et al 2007). The results showing that fear of pain is the mediating variable in the association between MC1R variant status and dental fear suggest that genetically influenced differences in pain experience (e.g., pain threshold, tolerance) may, in some cases, be foundational for the development of fear of pain, which may then underpin dental fear (see comment in Appendix).…”
Section: Figurementioning
confidence: 99%